Situational interest of students with autism spectrum disorder using context personalization in physical education - Verret, Claudia; Roure, Cédric; Ouellet, Cassandre; Massé, Line; Grenier, Johanne; Bergeron, Geneviève (European journal of adapted physical activity, 2022)
Physical education can enable students with autism spectrum disorder (ASD) to live positive experiences and adopt a healthy lifestyle. However, motivation may be a critical factor in their success. In this perspective, the context personalization approach could be valuable to support the interests and motivation of students with ASD in physical education. This qualitative interpretative research documents the Situational Interest dimensions of four high school male students with ASD (14 years old, boys) following a team sports unit conceived and personalized by their physical education teacher to meet their interest in video games. After the unit, the four students and the teacher realized a semi-structured interview. According to thematic analyses, students' situational interest was elicited. The dimensions of instant enjoyment, challenge and novelty were predominant. The emulation system, as a part of the context personalization related to video games, ends up in every dimension and sheds original light on the motivation conditions. In light of the present results, the context personalization approach, based on the interests and preferences of students, is a promising avenue to support interest in PE. However, differences between the students' and the teachers' perspectives underline the need to consider students' voices regarding their interest in physical education.
Keywords: tělesná výchova; Men; Adolescent; Physical Education and Training; lidé; muži; speciální vzdělávání; poruchy autistického spektra; Humans; postižené děti; Male; videohry; motivace; Video Games; Education, Special; Children with Disabilities; studenti; mužské pohlaví; Autism Spectrum Disorder; mladiství; Motivation; Students